The simultaneous quantification of cytochrome P450 dependent linoleate and arachidonate metabolites in urine by HPLC-MS/MS - Newman, John W.; Watanabe, Takaho; Hammock, Bruce D. (Journal of lipid research, 2002)
A method for the simultaneous quantification of urinary linoleic and arachidonic acid derived epoxides and diols, as well as the arachidonate omega hydroxylated product has been developed. The method employs negative mode electrospray ionization and HPLC with tandem mass spectroscopy for quantification. Odd chain length saturated epoxy and dihydroxy fatty acids are used as analytical surrogates resulting in linear calibrations (r (2) > or = 0.9995). Standard addition analyses showed that matrix effects do not prevent these surrogates from yielding reliable quantitative results. Using 4 ml urine aliquots at a final extract volume of 100 micro l and injecting 10 micro l, method detection limits and limits of quantification were < or =0.5 and 1.5 nM, respectively. The sensitivity for dihydroxy lipids was from 3- to 10-fold greater than the corresponding epoxy fatty acid. Shot to shot run times of 31 min were achieved. Rodent and human urine analyses indicated the method sensitivity is sufficient for general research applications. In addition, diurnal fluctuations in linoleate and arachidonate derived metabolites were observed in human subjects.